Electrochemical Behavior of Stainless Steels for Sudomotor Dysfunction Applications - Zagal-Moya, J; Zagal-Moya, J (Wiley-VCH Verlag, 2018)
AISI 304L is used in SudoscanTM technology (Impeto Medical Inc.) for the early diagnosis of small fiber neuropathy caused by type-2 diabetes or cystic fibrosis. In a recent paper, several substitute electrodes were analyzed, among which the biocompatible nickel-free AISI 430 appeared as an interesting material. In the present work, we compare in details the electrochemical behavior of AISI 430 with respect to the reference AISI 304L, using Electrochemical Impedance Spectroscopy (EIS) in mimetic electrolytic solutions of sweat. Apart of being cheaper than AISI 304L, AISI 430 has roughly similar characteristics but is slightly more sensitive to chloride ions concentration and, according to EIS and SEM analyses, forms a thicker, more homogeneous and protective oxide layer, which makes it a convenient electrode material. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim